Buffalo whey proteins as innovative raw material for nanoparticles building - Pablo A. Solis Cizek; Gustavo A. Crudeli; Darío Spelzini; Franco E. Vasile (Revista Científica)
Buffalo whey is the most important byproduct of the cheese industry. Whey proteins are fascinating from a technological and economic point of view. In the presence of polysaccharides (PS), proteins (PR) can form complexes in the na-noscale. The study of PS and PR interactions constitutes a key aspect in building nanomaterials, particularly when the use of scarcely studied protein sources such as Buffalo (Bubalus bubalis) whey is intended. In this sense, the objective of this work was to study the formation of biopolymeric structures by electrostatic interactions from buffalo whey proteins (BWPC) and Arabic gum (GA). An aqueous suspension containing BWPC (0.1% w/v) and GA (0.05% w/v) was prepared for this purpose. For comparative purposes, the behavior of mixtures containing cow whey (WPC) and GA, and the single components were also studied. The pH of biopolymeric dispersions was adjusted to 5.5 to 2.5 with HCl. The interactions were monitored through turbidimetric analysis (absorbance by spectrometry at 600 nm), zeta-potential and particle size distribution (by dynamic light scattering), and relative viscosity (in a Cannon-Fenske capillary viscometer). Analytical trials were performed at least in triplicate. Analysis of variance (ANOVA) was performed to find statistical differences among samples. The significance level was defined at p> 0.05 (confidence interval of 95%). While GA suspensions did not show changes in the absorbance, both BWPC and WPC displayed a maximum between pH 4 and 4.5, attributable to their isoelectric points. Comparatively, mixtures of BWPC-GA and WPC-GA showed higher turbidity values than single-component suspensions (p<0.05), which could indicate the occurrence of attractive interactions. The gradual increase in the absorbance, intended as the formation of soluble complexes, was verified for BWPC-GA from pH 5, reaching a maximum of 4. In contrast, for WPC-GA, it occurred between 5.5 and 4.5. In the range of formation of conjugates, PS-PR showed intermediate zeta-potential values to the single components, being -27 and -50 mV for BWPC-GA and WPC-GA, respectively. In these conditions, the particles showed a monomodal size distribution centered at 250 nm for both systems. The interaction between biopolymers at the different pH values did not evidence appreciable changes in the rheological properties (p>0.05). Obtained results allow us to consider that BWPC can undergo associative interactions with GA, resulting in soluble nano complexes with good colloidal valuable stability for the nutraceutical industry. The use of BWPC as nano-structured components constitutes a promising alternative for adding value to this byproduct, contributing to the economic benefit of dairy industries, and minimizing the polluting effect of this effluent.